Production of Verbascoside, Isoverbascoside and Phenolic Acids in Callus, Suspension, and Bioreactor Cultures of Verbena officinalis and Biological Properties of Biomass Extracts - Paweł Kubica; Agnieszka Szopa; Adam Kokotkiewicz; Natalizia Miceli; Maria Fernanda Taviano; Alessandro Maugeri; Santa Cirmi; Alicja Synowiec; Małgorzata Gniewosz; Hosam O. Elansary; Eman A. Mahmoud; Diaa O. El-Ansary; et al. (Molecules, 2020)
Callus, suspension and bioreactor cultures of Verbena officinalis were established, and optimized for biomass growth and production of phenylpropanoid glycosides, phenolic acids, flavonoids and iridoids. All types of cultures were maintained on/in the Murashige and Skoog (MS) media with 1 mg/L BAP and 1 mg/L NAA. The inoculum sizes were optimized in callus and suspension cultures. Moreover, the growth of the culture in two different types of bioreactors—a balloon bioreactor (BB) and a stirred-tank bioreactor (STB) was tested. In methanolic extracts from biomass of all types of in vitro cultures the presence of the same metabolites—verbascoside, isoverbascoside, and six phenolic acids: protocatechuic, chlorogenic, vanillic, caffeic, ferulic and rosmarinic acids was confirmed and quantified by the HPLC-DAD method. In the extracts from lyophilized culture media, no metabolites were found. The main metabolites in biomass extracts were verbascoside and isoverbascoside. Their maximum amounts in g/100 g DW (dry weight) in the tested types of cultures were as follow: 7.25 and 0.61 (callus), 7.06 and 0.48 (suspension), 7.69 and 0.31 (BB), 9.18 and 0.34 (STB). The amounts of phenolic acids were many times lower, max. total content reached of 26.90, 50.72, 19.88, and 36.78 mg/100 g DW, respectively. The highest content of verbascoside and also a high content of isoverbascoside obtained in STB (stirred-tank bioreactor) were 5.3 and 7.8 times higher than in extracts from overground parts of the parent plant. In the extracts from parent plant two iridoids—verbenalin and hastatoside, were also abundant. All investigated biomass extracts and the extracts from parent plant showed the antiproliferative, antioxidant and antibacterial activities. The strongest activities were documented for the cultures maintained in STB. We propose extracts from in vitro cultured biomass of vervain, especially from STB, as a rich source of bioactive metabolites with antiproliferative, antioxidant and antibacterial properties.